A fluoride solid electrolyte and its preparation method and its application in all-solid-state lithium-ion battery and its composite positive electrode

The fluoride solid electrolyte material synthesized by high-energy ball milling method solves the problems of high voltage stability of all-solid lithium batteries and insufficient ionic conductivity of the positive electrode material, and achieves the improvement of charging cutoff voltage and energy density.

CN119315037BActive Publication Date: 2025-03-25DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411834704.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-25
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The problem of insufficient high voltage stability of the solid electrolyte in all-solid-state lithium batteries and insufficient ionic conductivity of the positive electrode material makes it difficult to improve the charging cutoff voltage and the energy density of the positive electrode.

Method used

A fluoride solid electrolyte material is synthesized in one step by high-energy ball milling method, which has high lithium ion conductivity and good ion transmission performance. It can serve as a supporting electrolyte for all-solid lithium batteries, increase the charging cutoff voltage, and have the ability to reversibly deintercalate lithium ions.

Benefits of technology

The high voltage stability and high energy density of all solid-state lithium batteries have been achieved, the charging cut-off voltage is increased to 4.5 V, the specific capacity at the positive electrode level is increased by more than 20%, and the energy density is increased by more than 15%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315037B_ABST
    Figure CN119315037B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of solid electrolytes for all-solid-state lithium-ion batteries, and particularly relates to a fluoride solid electrolyte and a preparation method thereof, as well as applications in all-solid-state lithium-ion batteries and composite positive electrodes thereof. The fluoride solid electrolyte is synthesized in one step from three raw materials, LiCl, Li2O and FeF3, through a high-energy ball milling reaction; the ionic conductivity of the fluoride solid electrolyte reaches 2.8 mS cm ‑1 , as the positive electrode supporting electrolyte in the all-solid-state lithium battery, to achieve an increase in the energy density at the electrode level; the fluoride solid electrolyte material also has a capacity of more than 250 mAh g ‑1 reversible capacity; when the fluoride solid electrolyte that can contribute capacity is used as the positive electrode supporting electrolyte and matched with the ternary positive electrode material, the specific capacity of the positive electrode layer of the all-solid-state lithium battery is increased by more than 20%, the energy density is increased by more than 15%, and the cycle stability of the whole battery at a high cut-off voltage is significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of all-solid-state lithium-ion batteries, and in particular relates to a fluoride solid electrolyte and a preparation method thereof, as well as applications in all-solid-state lithium-ion batteries and composite positive electrodes thereof. Background Art

[0002] New energy vehicles are an important part of achieving the dual carbon goals. Developing secondary batteries with high specific energy, high safety and wide temperature range is an effective strategy to promote the development of new energy vehicles. Lithium-ion batteries have the advantages of high specific energy, long cycle life, low self-discharge and no memory effect, and they dominate the global secondary battery market. All-solid-state lithium batteries use non-flammable solid electrolytes matched with lithium metal negative electrodes, and have the characteristics of high energy density and intrinsic safety. They are the main candidates for the next generation of high specific energy lithium-ion batteries.

[0003] At present, all-solid-state lithium batteries have made considerable progress in the ionic conductivity and electrochemical stability of solid electrolytes, but there are still some problems that limit the further improvement of the energy density of all-solid-state lithium batteries: First, the high-voltage stability of solid electrolytes is insufficient, and it is difficult to increase the charging cut-off voltage to above 4.5 V to match the high-voltage positive electrode material, which makes it difficult for all-solid-state lithium batteries to give full play to the high specific capacity advantages of high-voltage lithium cobalt oxide, high-nickel ternary materials, and lithium-rich positive electrode materials under high voltage; Second, in the positive electrode of all-solid-state lithium batteries, due to the insufficient ionic conductivity of the positive electrode material, it is difficult to conduct lithium ions. It is necessary to add 20~30 wt% of solid electrolyte as a supporting electrolyte to the composite positive electrode. Since the supporting electrolyte cannot contribute to capacity, the higher the supporting electrolyte content in the composite positive electrode, the lower the positive electrode energy density, but reducing the content of the positive electrode supporting electrolyte will affect the construction of the ion transport network, and thus affect the battery's rate performance.

[0004] In response to the problem of insufficient high-voltage stability of solid electrolytes, the current mainstream research direction is to use fluorine elements with outstanding high-voltage stability for doping or directly develop fluoride solid electrolytes. However, due to the strong electrostatic interaction between Li and F, the ionic conductivity of fluorine-containing solid electrolytes is difficult to improve. In response to the problem that the addition of supporting electrolytes in composite positive electrodes creates a trade-off between the energy density and power density of the positive electrode, the current mainstream idea is to improve the ionic conductivity of the supporting electrolyte. However, the electrochemical stability of mainstream high-ion conductivity materials is insufficient, resulting in a faster attenuation of the positive electrode material when used as a supporting electrolyte. At the same time, the introduction of high-ion conductivity supporting electrolytes also has a minimum value for building a stable ion transport network, which does not fundamentally solve the problem of reduced energy density at the positive electrode level. Summary of the invention

[0005] In view of the above-mentioned technical problems, the present invention provides a fluoride solid electrolyte and a preparation method thereof as well as an application in an all-solid-state lithium-ion battery and a composite positive electrode thereof. The present invention synthesizes a fluoride solid electrolyte material that can contribute capacity in one step by high-energy ball milling, and the room temperature ionic conductivity reaches 2.8 mS cm -1 The activation energy is as low as 0.27 eV, and it has good ion transport performance. It can be used as a supporting electrolyte in the composite positive electrode of all-solid-state lithium batteries, and the charging cut-off voltage of the all-solid-state lithium battery for stable cycling is increased to 4.5 V. At the same time, the material itself has the ability to reversibly insert and deinsert lithium ions. After being combined with conductive carbon, it can contribute more than 250 mAh g as a positive electrode active material. -1 The reversible capacity of the all-solid-state lithium battery can be increased by more than 20% and the energy density by more than 15% when it is matched with the ternary positive electrode material.

[0006] In order to achieve the above object, the technical solution adopted by the present invention includes:

[0007] In the first aspect, the present invention provides a fluoride solid electrolyte, which is composed of five elements: lithium, iron, oxygen, fluorine, and chlorine, and has a general chemical composition formula of xLiCl+yLi2O+FeF3, wherein x represents the molar ratio of LiCl to FeF3, y represents the molar ratio of Li2O to FeF3, 0.1≤x≤1.2 (preferably 0.2≤x≤1), 0.1≤y≤3 (preferably 0.2≤y≤2.8).

[0008] Furthermore, the particles of the solid electrolyte are in irregular block shape.

[0009] The fluoride solid electrolyte of the present invention has a structural feature of mainly an amorphous phase, high lithium ion conductivity and stable charge and discharge capabilities. It can be used as a supporting electrolyte for an all-solid-state lithium battery to match a high-voltage positive electrode material, and while conducting lithium ions, it contributes additional capacity, thereby achieving an increase in the energy density of the all-solid-state electrolyte.

[0010] In a second aspect, the present invention provides a method for preparing a fluoride solid electrolyte with capacity contribution, the method comprising the following steps:

[0011] Step 1, weighing lithium oxide, lithium chloride and ferric fluoride raw materials and mixing them evenly;

[0012] Step 2, adding the mixed raw materials in step 1 into a ball mill, adding ball mill beads into the mill, and then sealing the mill;

[0013] Step 3, placing the ball mill in step 2 in a high-speed ball mill for high-energy ball milling reaction;

[0014] Step 4, grinding the product obtained in step 3 to obtain the fluoride solid electrolyte.

[0015] Furthermore, lithium oxide and lithium chloride are used as lithium sources, and iron fluoride is used as an iron source, wherein the lithium oxide is Li2O or Li2O2, and the iron fluoride is FeF3.

[0016] Further, in step 1, the molar ratio of lithium oxide: lithium chloride: ferric fluoride is (0.1-3): (0.1-1.2): 1, preferably (0.2-2.8): (0.2-1): 1;

[0017] In step 3, the specific process of the high-energy ball milling reaction is that the ball milling speed is 300-2000 rpm, preferably 500-1000 rpm; and the ball milling reaction time is 5-50 h.

[0018] In a third aspect, the present invention provides an all-solid-state lithium-ion battery composite positive electrode, the all-solid-state lithium-ion battery composite positive electrode comprising the fluoride solid electrolyte and a conductive agent; the mass content of the conductive agent in the composite positive electrode accounts for 1-3% of the total mass of the composite electrode;

[0019] Alternatively, the all-solid-state lithium-ion battery composite positive electrode comprises the fluoride solid electrolyte and the positive electrode material; the mass content of the positive electrode material in the composite positive electrode accounts for 50-80% of the total mass of the composite electrode.

[0020] Furthermore, the conductive agent is one or more of carbon nanotubes, carbon nanofibers, graphene, SuperP, Ketjen black, acetylene black, and activated carbon;

[0021] The positive electrode material is one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, and nickel cobalt lithium manganese oxide.

[0022] In a fourth aspect, the present invention provides an all-solid-state lithium-ion battery, wherein the positive electrode of the all-solid-state lithium-ion battery adopts the all-solid-state lithium-ion battery composite positive electrode.

[0023] Furthermore, a solid electrolyte is used as a separator, and a lithium metal foil or a lithium alloy is used as a negative electrode.

[0024] Furthermore, the solid electrolyte is one of an oxide-type solid electrolyte, a fluoride-type solid electrolyte, a halide-type and a sulfide-type double-layer solid electrolyte.

[0025] The oxide-type solid electrolyte is one of lanthanum lithium titanate (LLTO), lanthanum lithium zirconate (LLZO), and lithium aluminum titanium phosphate (LATP).

[0026] The fluoride-type solid electrolyte is one of Li3AlF6 and Li3GaF6.

[0027] The halide and sulfide double-layer solid electrolyte is a halide electrolyte Li3InCl6, Li3YCl6, LI2ZrCl6 and a sulfide electrolyte Li6PS5Cl, Li 10 GeP2S 12 A component of .

[0028] The beneficial effects of the present invention are:

[0029] (1) The fluoride solid electrolyte of the present invention realizes the amorphization of fluoride materials through anion mixing reaction mechanism and high-energy ball milling reaction, and improves the ionic conductivity of the fluoride solid electrolyte to the mS level. This type of fluoride solid electrolyte has good ion transport performance and can be used as a positive electrode supporting electrolyte for all-solid-state lithium batteries.

[0030] (2) The fluoride solid electrolyte material described in the present invention has excellent high-voltage stability. When matched with an uncoated high-voltage positive electrode material, it can ensure that the battery still has excellent cycle stability when the charging cut-off voltage is 4.5 V, which significantly improves the capacity of the high-voltage positive electrode material and improves the energy density of the all-solid-state lithium battery.

[0031] (3) The fluoride solid electrolyte material described in the present invention has a reversible capacity contribution of up to 250 mAh g-1. After being compounded with conductive carbon, it can be directly used as a positive electrode active material. When used as a supporting electrolyte, it can increase the specific capacity of the positive electrode layer of the all-solid-state lithium battery by more than 20% and the energy density by more than 15%.

[0032] (4) The high ion conductive cathode material described in the present invention uses iron, which is a relatively abundant element in the earth's crust, as its raw material. Compared with halide electrolytes using rare earth metal elements, this effectively reduces the raw material cost of the material. At the same time, it only requires one step of high-energy ball milling to synthesize, and the process complexity is relatively low, which has good prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a SEM image of the fluoride solid electrolyte material prepared in Example 1;

[0034] Figure 2 Arrhenius curves of ionic conductivity of materials in Examples 1-5 at different temperatures;

[0035] Figure 3 The EIS curves of Example 1 and Comparative Examples 4 and 5 at room temperature;

[0036] Figure 4 X-ray diffraction spectra of the fluoride solid electrolyte materials prepared in Examples 1-5;

[0037] Figure 5 The specific capacity test results of the materials of Examples 1-5 are as follows;

[0038] Figure 6 This is a cycle performance diagram of the composite positive electrode material prepared in Example 1 for specific capacity testing;

[0039] Figure 7 The charge and discharge curves of the composite positive electrode materials prepared in Example 1 and Comparative Examples 4 and 5 in all-solid-state lithium batteries;

[0040] Figure 8 This is a comparison chart of the cycle performance of the positive electrode materials prepared in Example 1 and Comparative Examples 4 and 5 in all-solid-state lithium batteries;

[0041] Fig. 9 This is a rate performance diagram of the all-solid-state lithium battery in Example 1. DETAILED DESCRIPTION

[0042] Example 1

[0043] Synthesis of fluoride solid electrolyte material: Weigh 0.0890g Li2O, 0.2493g LiCl and 0.6627g FeF3 (corresponding to the reactant molar ratio of 0.5:1:1) respectively, and grind with a mortar for more than 10 min to mix the reactants evenly. Put the mixed sample into a zirconium dioxide ball mill, add 75g of zirconium dioxide ball milling beads with a total mass, wherein the number ratio of ball milling beads with different diameters is 10 mm:8 mm:5 mm=1:10:5, and seal the ball mill. Place the ball mill on a high-speed ball mill with a speed of 1000 rpm and high-energy ball milling for 8 h. Scrape the reacted sample from the ball mill and grind it appropriately with a mortar until there is no obvious block to obtain Example 1 of fluoride solid electrolyte material.

[0044] The blocking electrode method was used to measure the ionic conductivity of the material: a Beijing Zhongke Wanyuan two-electrode ionic conductivity test cell with an inner diameter of 10 mm was used, 100 mg of fluoride solid electrolyte material powder was added, and it was placed on a press and a pressure of 4t was applied for 3 minutes. The overall thickness of the battery after adding the fluoride solid electrolyte material powder was measured, and the thickness of the positive electrode material sheet was calculated to be 0.46 mm. The mold battery was connected to the electrochemical workstation for EIS testing, with a voltage polarization of 100 mV and a frequency range of 1 Hz-7 MHz. When measuring at different temperatures, the mold battery was placed in a high and low temperature box at the corresponding temperature for 1 h before EIS measurement. The temperature range was -15~65 o C, the temperature gradient is 20 o C.

[0045] Preparation of composite positive electrode for specific capacity test: Weigh 180 mg of fluoride solid electrolyte material and 20 mg of Ketjen black respectively, and grind them in a mortar for more than 10 min to mix the reactants evenly. Put the mixed sample into a ball mill, add 50 g of ball milling beads with different diameters in a ratio of 10 mm: 8 mm: 5 mm = 1: 10: 5, and seal the ball mill. Place the ball mill on a high-speed ball mill and mill at 550 rpm for 4 h. Scrape the sample out of the ball mill to obtain a composite positive electrode material for specific capacity test.

[0046] Preparation of composite positive electrode for all-solid-state lithium battery test: Weigh 90 mg of fluoride solid electrolyte material and 210 mg of uncoated nickel cobalt manganese oxide material (where Ni content accounts for 85% of transition metal elements) respectively, and grind with a mortar for more than 10 min to mix the reactants evenly. Put the mixed sample into a ball mill, add 50 g of ball milling beads with different diameters, and the ratio of the number of ball milling beads is 10 mm: 8 mm: 5 mm = 1: 10: 5, and seal the ball mill. Place the ball mill on a high-speed ball mill and mill at 200 rpm for 0.5 h. Scrape the sample out of the ball mill to obtain the composite positive electrode material for all-solid-state lithium battery test.

[0047] All-solid-state lithium-ion battery assembly: Use a Beijing Zhongke Wanyuan solid-state two-electrode pressure-controlled mold with an inner diameter of 10 mm, add 50 mgLi2ZrCl6 (preparation method see Comparative Example 4) and 50 mg Li6PS5Cl (China Research Institute of Technology Co., Ltd., model SB06F), place it on a press and apply 1 t pressure for 1 min. Weigh 2 mg of composite positive electrode material (when testing specific capacity, the above-mentioned specific capacity test composite positive electrode material is selected; when testing the stability of all-solid-state lithium batteries, the above-mentioned all-solid-state lithium battery test composite positive electrode material is selected), evenly spread on one side of Li2ZrCl6, and then place it on a press to apply 4 t pressure for 3 min. Attach a 50μm thick lithium foil and a copper foil on one side of Li6PS5Cl to maintain the battery at a running pressure of 1 t. The specific capacity is obtained by constant current charge and discharge test measurement, and the current density is 0.1 mA cm -2 The charge and discharge voltage range is 1.0~4.5 V. The stability test of all-solid-state lithium battery is obtained by constant current charge and discharge cycle test, and the current density used is 0.1 mAcm -2 The charge and discharge voltage range is 3.0~4.5 V. The current density used in the rate test of all-solid-state lithium battery is 0.1 mA cm -2 , 0.2 mA cm -2 , 0.5 mA cm -2 , 1 mA cm -2 and 2 mA cm-2 , 5 charge and discharge cycles were performed at each current density, and the charge and discharge voltage range was 3.0~4.5 V.

[0048] Example 2

[0049] Synthesis of fluoride solid electrolyte material: 0.1005 g Li2O, 0.1424 g LiCl and 0.7571 g FeF3 (corresponding to a reactant molar ratio of 0.5:0.5:1) were weighed respectively and ground in a mortar for more than 10 min to make the reactants uniformly mixed. The subsequent synthesis steps were the same as in Example 1.

[0050] The method for measuring the ionic conductivity of the material using the blocking electrode method is the same as in Example 1.

[0051] Specific capacity test The preparation of the composite positive electrode is the same as in Example 1.

[0052] Example 3

[0053] Synthesis of fluoride solid electrolyte material: 0.0573 g Li2O, 0.0811 g LiCl and 0.8626 g FeF3 (corresponding to a reactant molar ratio of 0.25:0.25:1) were weighed respectively and ground in a mortar for more than 10 min to make the reactants uniformly mixed. The subsequent synthesis steps were the same as in Example 1.

[0054] The method for measuring the ionic conductivity of the material using the blocking electrode method is the same as in Example 1.

[0055] Specific capacity test The preparation of the composite positive electrode is the same as in Example 1.

[0056] Example 4

[0057] Synthesis of fluoride solid electrolyte material: 0.3579 g Li2O, 0.1015 g LiCl and 0.5406 g FeF3 (corresponding to a reactant molar ratio of 2.5:0.5:1) were weighed respectively and ground in a mortar for more than 10 min to make the reactants uniformly mixed. The subsequent synthesis steps were the same as in Example 1.

[0058] The method for measuring the ionic conductivity of the material using the blocking electrode method is the same as in Example 1.

[0059] Specific capacity test The preparation of the composite positive electrode is the same as in Example 1.

[0060] Example 5

[0061] Synthesis of fluoride solid electrolyte material: 0.1292 g Li2O2, 0.2378 g LiCl and 0.6330 g FeF3 (corresponding to a reactant molar ratio of 0.5:1:1) were weighed respectively and ground in a mortar for more than 10 min to make the reactants uniformly mixed. The subsequent synthesis steps were the same as in Example 1.

[0062] The method for measuring the ionic conductivity of the material using the blocking electrode method is the same as in Example 1.

[0063] Specific capacity test The preparation of the composite positive electrode is the same as in Example 1.

[0064] Comparative Example 1

[0065] Synthesis of fluoride solid electrolyte material: 0.0890 g Li2O, 0.2493 g LiCl and 0.6627 g FeF3 (corresponding to a reactant molar ratio of 0.5:1:1) were weighed respectively, and ground in a mortar for more than 10 min to mix the reactants evenly. The subsequent synthesis steps were the same as in Example 1, the ball mill speed was set to 200 rpm, and the reaction was carried out for 8 h.

[0066] The method for measuring the ionic conductivity of the material using the blocking electrode method is the same as in Example 1.

[0067] The preparation method of the composite positive electrode is the same as that of Example 1.

[0068] The assembly method of the all-solid-state lithium-ion battery is the same as that of Example 1.

[0069] Comparative Example 2

[0070] Synthesis of fluoride solid electrolyte material: 0.0890 g Li2O, 0.2493 g LiCl and 0.6627 g FeF3 (corresponding to a reactant molar ratio of 0.5:1:1) were weighed respectively, and ground in a mortar for more than 10 min to mix the reactants evenly. The subsequent synthesis steps were the same as in Example 1, the ball mill speed was set to 1000 rpm, and the reaction was carried out for 2 h.

[0071] The method for measuring the ionic conductivity of the material using the blocking electrode method is the same as in Example 1.

[0072] The preparation method of the composite positive electrode is the same as that of Example 1.

[0073] The assembly method of the all-solid-state lithium-ion battery is the same as that of Example 1.

[0074] Comparative Example 3

[0075] Synthesis of fluoride solid electrolyte material: 0.0989 g Li2O, 0.2806 g LiCl and 0.6212 g FeF2 (corresponding to a reactant molar ratio of 0.5:1:1) were weighed respectively, and ground in a mortar for more than 10 min to mix the reactants evenly. The subsequent synthesis steps were the same as in Example 1.

[0076] The method for measuring the ionic conductivity of the material using the blocking electrode method is the same as in Example 1.

[0077] The preparation method of the composite positive electrode is the same as that of Example 1.

[0078] The assembly method of the all-solid-state lithium-ion battery is the same as that of Example 1.

[0079] Comparative Example 4

[0080] Synthesis of halide solid electrolyte Li2ZrCl6: Weigh 0.2641 g LiCl and 0.7359 g ZrCl4 respectively and grind them in a mortar to mix evenly. Put the mixed sample into a ball mill, add 75 g of ball milling beads, where the number ratio of ball milling beads with different diameters is 10 mm: 8 mm: 5 mm = 1: 10: 5, and seal the ball mill. Place the ball mill on a high-speed ball mill at a speed of 1000 rpm and perform high-energy ball milling for 8 h. Scrape the reacted sample from the ball mill and grind it properly with a mortar until there is no obvious block to obtain the halide solid electrolyte material Li2ZrCl6 comparative example 4.

[0081] The blocking electrode method for measuring the ionic conductivity of the material was the same as in Example 1, and the thickness of the positive electrode material sheet was measured to be 0.43 mm.

[0082] The method for preparing the composite positive electrode of the all-solid-state lithium battery is the same as that in Example 1.

[0083] The assembly method of the all-solid-state lithium-ion battery is the same as that of Example 1.

[0084] Comparative Example 5

[0085] Synthesis of halide solid electrolyte Li3GaF6: 0.4433 g Li2CO3 added to 10 mL C 10 Bmim ionic liquid, keep warm and stir at 60 ℃ for 6 h; then add 1.246 g GaCl3·H2O into the ionic liquid, keep warm and stir at 60 ℃ for 12 h, and naturally cool to room temperature; the precipitate is washed with acetone 4 times and then vacuum dried at 80 ℃ overnight to obtain the fluoride solid electrolyte material Li3GaF6 comparative example 5.

[0086] The blocking electrode method for measuring the ionic conductivity of the material was the same as in Example 1, and the thickness of the positive electrode material sheet was measured to be 0.36 mm.

[0087] The method for preparing the composite positive electrode of the all-solid-state lithium battery is the same as that in Example 1.

[0088] The assembly method of the all-solid-state lithium-ion battery is the same as that of Example 1.

[0089] The solid electrolyte synthesis methods of Examples 1-5 and Comparative Examples 1-3 and some test results are summarized in Table 1:

[0090] Table 1: Solid electrolyte synthesis method and some test results

[0091] Reactants and composition Reaction conditions <![CDATA[Room temperature ionic conductivity (mS cm -1 )]]> Phase composition <![CDATA[Specific capacity (mAh g -1 )]]> Example 1 <![CDATA[LiCl+0.5Li2O+FeF3]]> 1000rpm8h 2.692 Mainly amorphous components, with a small amount of LiF and LiCl microcrystals 273.0 Example 2 <![CDATA[0.5LiCl+0.5Li2O+FeF3]]> 1000rpm8h 0.912 Mainly amorphous components, with a small amount of LiF microcrystals 240.8 Example 3 <![CDATA[0.25LiCl+0.25Li2O+FeF3]]> 1000rpm8h 0.091 Mainly amorphous components 178.6 Example 4 <![CDATA[0.5LiCl+2.5Li2O+FeF3]]> 1000rpm8h 0.087 Mainly crystalline LiF and LiCl, with amorphous components 228.7 Example 5 <![CDATA[LiCl+0.5Li2O2+FeF3]]> 1000rpm8h 0.200 Mainly amorphous components, with a small amount of LiF and LiCl microcrystals 282.6 Comparative Example 1 <![CDATA[LiCl+0.5Li2O+FeF3]]> 200rpm8h <![CDATA[<10 -5 ]]> The reactants have not reacted completely 10.6 Comparative Example 2 <![CDATA[LiCl+0.5Li2O+FeF3]]> 1000rpm2h <![CDATA[<10 -5 ]]> The reactants have not reacted completely 15.7 Comparative Example 3 <![CDATA[LiCl+0.5Li2O+FeF2]]> 1000rpm8h <![CDATA[<10 -5 ]]> The reactants have not reacted completely 2.5

[0092] Experimental results analysis:

[0093] SEM characterization was performed on Example 1, and the results were as follows Figure 1 As shown. From the SEM results, it can be seen that the particle size of the prepared fluoride solid electrolyte is 2~10 um. The smaller particle diameter ensures that the material can more efficiently build an ion transport network in the all-solid-state lithium battery composite positive electrode and achieve a higher compaction density.

[0094] The five solid electrolytes of Examples 1-5 were characterized by variable temperature EIS, and the ionic conductivities of the five solid electrolyte materials at different temperatures were calculated to obtain the Arrhenius curves as shown in FIG. Figure 2 As shown. At room temperature (25 o C), the ionic conductivity of the fluoride solid electrolyte corresponding to Example 1 is 2.8 mS cm -1 , indicating that the fluoride solid electrolyte material prepared by the present invention has a relatively high ionic conductivity; the ionic conductivity of Examples 2-4 is all 0.087 mS cm -1 The above indicates that the material can accept non-stoichiometric synthesis within a certain range; the ionic conductivity and activation energy of Example 5 are close to those of Example 1, indicating that both Li2O and Li2O2 can be used to synthesize the target solid electrolyte. The lithium ion transfer activation energy of Example 1 calculated from the slope of the Arrhenius curve is 0.27 eV, indicating that the fluoride solid electrolyte material prepared by the present invention has a low ion transfer activation energy, that is, the material has a lower lithium ion transfer barrier. High ionic conductivity and low ion transfer activation energy are the basic characteristics of the fluoride solid electrolyte material described in the present invention as a positive electrode supporting electrolyte. As Figure 3 As shown, compared with the commonly used halide solid electrolyte Li2ZrCl6 (room temperature ionic conductivity 0.72 mS cm) shown in Comparative Example 4 -1 ) and the fluoride solid electrolyte Li3GaCl6 shown in Comparative Example 5 (room temperature ionic conductivity 0.088 mS cm -1 ), the fluoride electrolyte corresponding to Example 1 has higher ionic conductivity and is more suitable as a positive electrode supporting electrolyte for an all-solid-state lithium battery.

[0095] XRD characterization was performed on Examples 1-5, and the results were as follows Figure 4As shown. From the XRD spectrum, the fluoride electrolyte materials corresponding to Examples 1 and 5 are mainly amorphous phase components. The amorphous phase has the characteristics of low grain boundary ion transmission resistance, ion percolation transmission characteristics, and isotropic ion transmission characteristics, which is the reason why the material has good ion transmission performance. There are also some crystalline phase components in the material. After retrieval, the corresponding LiCl, LiF, and FeOCl crystallites are partly reaction products. A small amount of crystalline phase components can form a fast ion transmission path along the grain boundary, further improving the ionic conductivity of the material. It was determined by XRD and solid nuclear magnetic characterization that the content of the crystalline phase in Example 1 is less than 20 mol%. In Example 2, except for the amorphous phase component, the main crystalline phase component is only LiF, but the ionic conductivity is lower than that of Example 1; in Example 3, the crystalline phase content is lower and has lower ionic conductivity, so it is speculated that crystalline LiCl contributes to ionic conductivity. In Example 4, the crystalline phase component is obvious, and the amorphous phase content is less, so the ionic conductivity is lower, so the amorphous phase component also contributes to the ionic conductivity.

[0096] The fluoride electrolyte materials of Examples 1-5 were combined with conductive carbon to construct a composite positive electrode, and the specific capacity reversible cycle performance of the fluoride electrolyte material itself was tested. Figure 5 , 6 The test results show that the fluoride electrolyte material itself has a maximum capacity of 275 mAh g -1 The reversible capacity is exerted, and the capacity retention rate after 150 cycles is 83.4%, indicating that the material itself has good cycle stability, indicating that it can contribute additional capacity when used as a positive electrode supporting electrolyte for all-solid-state lithium batteries.

[0097] The fluoride electrolyte material is used as the supporting electrolyte to match the high-nickel ternary positive electrode material, that is, the composite positive electrode material corresponding to Example 2, and a constant current charge and discharge test and a rate performance test are performed. At the same time, the halide electrolyte material Li2ZrCl6 and the fluoride solid electrolyte Li3GaCl6 are used as comparative supporting electrolyte materials, that is, the composite positive electrode materials corresponding to Examples 4 and 5 are used for constant current charge and discharge tests, and the first cycle voltage-capacity comparison curve is obtained as shown in FIG. Figure 7 , long cycle performance comparison curve as follows Figure 8 , the rate performance curve is as follows Fig. 9 .Depend on Figure 7 The first cycle voltage-capacity comparison curve shows that when the fluoride solid electrolyte prepared by the present invention is used as the positive electrode supporting electrolyte, the all-solid-state lithium battery can exert additional capacity. Compared with the use of chloride electrolyte Li2ZrCl6, the specific capacity calculated by the composite positive electrode is increased by 22.2%, and the energy density is increased by 18.1%. Compared with the use of fluoride electrolyte Li3GaCl6, it has a smaller charge and discharge polarization; Figure 8The corresponding long cycle performance comparison curve shows that when the fluoride solid electrolyte prepared by the present invention is used as the positive electrode supporting electrolyte, the all-solid-state lithium battery can be stably cycled at a high charging cut-off voltage of 4.5 V, and the capacity retention rate is 84.2% after 200 cycles. The cycle stability is significantly higher than that of Comparative Example 4 using a chloride electrolyte and Comparative Example 5 using a fluoride electrolyte. Fig. 9 The corresponding rate performance curve shows that when the fluoride solid electrolyte prepared by the present invention is used as the positive electrode supporting electrolyte, the all-solid-state lithium battery has a rate performance of 2 mA cm -2 The capacity at a current density of 0.1 mA cm -2 The current density is 29.1%, indicating that it has good rate performance.

Claims

1. An all-solid-state lithium-ion battery composite positive electrode, characterized in that: The all-solid-state lithium-ion battery composite positive electrode is composed of a fluoride solid electrolyte and a conductive agent; the mass content of the conductive agent in the composite positive electrode accounts for 1-3% of the total mass of the composite electrode; The fluoride solid electrolyte is composed of five elements: lithium, iron, oxygen, fluorine and chlorine, and has a general chemical composition formula of xLiCl+yLi2O+FeF3, wherein x represents the molar ratio of LiCl to FeF3, y represents the molar ratio of Li2O to FeF3, and 0.5≤x≤1.2 and 0.5≤y≤3.

2. The all-solid-state lithium-ion battery composite positive electrode according to claim 1, characterized in that: The solid electrolyte particles are in irregular block shape.

3. An all-solid-state lithium-ion battery composite positive electrode according to any one of claims 1 to 2, characterized in that: The preparation method of the fluoride solid electrolyte comprises the following steps: Step 1, weighing lithium oxide, lithium chloride and ferric fluoride raw materials and mixing them evenly; Step 2, adding the mixed raw materials in step 1 into a ball mill, adding ball mill beads into the mill, and then sealing the mill; Step 3, placing the ball mill in step 2 in a high-speed ball mill for high-energy ball milling reaction; Step 4, grinding the product obtained in step 3 to obtain the fluoride solid electrolyte.

4. The all-solid-state lithium-ion battery composite positive electrode according to claim 3, characterized in that: In step 1, the molar ratio of lithium oxide: lithium chloride: iron fluoride is (0.5-3): (0.5-1.2): 1; In step 3, the specific process of the high-energy ball milling reaction is that the ball milling speed is 300-2000 rpm and the ball milling reaction time is 5-50h.

5. The all-solid-state lithium-ion battery composite positive electrode according to claim 3, characterized in that: Lithium oxide and lithium chloride are used as lithium sources, and ferric fluoride is used as an iron source, wherein the lithium oxide is Li2O and the ferric fluoride is FeF3.

6. The all-solid-state lithium-ion battery composite positive electrode according to claim 1, characterized in that: The conductive agent is one or more of carbon nanotubes, carbon nanofibers, graphene, SuperP, Ketjen black, acetylene black, and activated carbon.

7. An all-solid-state lithium-ion battery, characterized in that: The positive electrode of the all-solid-state lithium-ion battery adopts the all-solid-state lithium-ion battery composite positive electrode described in any one of claims 1-6.

8. The all-solid-state lithium-ion battery according to claim 7, characterized in that: A solid electrolyte is used as the separator and lithium metal foil or lithium alloy is used as the negative electrode.

9. The all-solid-state lithium-ion battery according to claim 7, characterized in that: The solid electrolyte is one of an oxide-type solid electrolyte, a fluoride-type solid electrolyte, a halide-type and a sulfide-type double-layer solid electrolyte.

Citation Information

Patent Citations

  • Amorphous solid electrolyte material and preparation method and application thereof

    CN114792839A

  • Halide-based solid electrolyte with capacity output and application of halide-based solid electrolyte in solid-state lithium battery

    CN118117151A

  • Novel oxyhalide solid electrolyte stable to lithium metal, preparation method of novel oxyhalide solid electrolyte and all-solid-state lithium metal battery

    CN118763268A